Collaboration in academic research in the field of Business and Management in France: Intranational versus international - Amdaoud, Mounir; Laurens, Patricia; Le Bas, Christian; Vo, Linh-Chi (Management international / International Management / Gestiòn Internacional, 2024)
Research collaboration is now the norm in the academic community. The literature has widely discussed the benefits and costs of research collaboration and compared across collaboration types (intranational, international). A discussion is still missing about collaboration in business and management as a separate discipline in the French context characterized by a separation between private business schools and public universities. The literature has rarely examined how international and intranational collaborations differ in terms of scale, scope, and impact. The purpose of this study is to address these two gaps through the notion of trade-off by using bibliometric measures of co-authorship.